Chaperone-Mediated Autophagy in Neurodegenerative Diseases: Molecular Mechanisms and Pharmacological Opportunities - Wang, Yi-Ting; Lu, Jia-Hong (Cells (Basel, Switzerland), 2022)
Chaperone-mediated autophagy (CMA) is a protein degradation mechanism through lysosomes. By targeting the KFERQ motif of the substrate, CMA is responsible for the degradation of about 30% of cytosolic proteins, including a series of proteins associated with neurodegenerative diseases (NDs). The fact that decreased activity of CMA is observed in NDs, and ND-associated mutant proteins, including alpha-synuclein and Tau, directly impair CMA activity reveals a possible vicious cycle of CMA impairment and pathogenic protein accumulation in ND development. Given the intrinsic connection between CMA dysfunction and ND, enhancement of CMA has been regarded as a strategy to counteract ND. Indeed, genetic and pharmacological approaches to modulate CMA have been shown to promote the degradation of ND-associated proteins and alleviate ND phenotypes in multiple ND models. This review summarizes the current knowledge on the mechanism of CMA with a focus on its relationship with NDs and discusses the therapeutic potential of CMA modulation for ND.